1988
DOI: 10.1111/j.1399-0039.1988.tb02063.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA antigens and periodontal disease

Abstract: HLA-A, B and DR antigen frequencies were determined in three groups of periodontally diagnosed subjects: 49 patients with rapidly progressive periodontitis, 40 elderly subjects with minimal disease (considered as a resistant group) and 30 young subjects with minimal disease. The relative risk for HLA-A9 (previously reported to be associated with periodontal disease) was 15.5. HLA-A9 was present in 36.7% of the patients and 2.5% of the resistant group. HLA-A10 showed a significantly increased incidence in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
3
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 16 publications
1
31
3
4
Order By: Relevance
“…Studies of adult periodontal disease have primarily included teenagers and young adults, and in some instances it has been unclear if the individuals with periodontal disease had early-onset, rather than adult, periodontal disease. These studies have for the most part shown a lower frequency of HLA-A2 among those subjects with periodontal disease (Kaslick et al, , 1980Terasaki et al, 1975), and a higher frequency of HLA-A9 (Klouda et al, 1986;Amer et al, 1988). Association studies of clear cases of adult periodontal disease, as well as family-based genetic linkage studies, may prove helpful in clarifying the relationship between HLA antigens and the genetics of periodontal disease susceptibility.…”
Section: Population Association Studiesmentioning
confidence: 99%
“…Studies of adult periodontal disease have primarily included teenagers and young adults, and in some instances it has been unclear if the individuals with periodontal disease had early-onset, rather than adult, periodontal disease. These studies have for the most part shown a lower frequency of HLA-A2 among those subjects with periodontal disease (Kaslick et al, , 1980Terasaki et al, 1975), and a higher frequency of HLA-A9 (Klouda et al, 1986;Amer et al, 1988). Association studies of clear cases of adult periodontal disease, as well as family-based genetic linkage studies, may prove helpful in clarifying the relationship between HLA antigens and the genetics of periodontal disease susceptibility.…”
Section: Population Association Studiesmentioning
confidence: 99%
“…Periodontal hastalığın başlaması ve ilerlemesinde etkili interleukin-1 (IL-1), tümör nekroz faktörü-α (TNF-α) gibi sitokinler, insan lökosit antijenleri (HLA) ve matris metalloproteinazlar (MMPs), katepsin-C, vitamin D gibi proteaz ve yapısal moleküllerin ekspresyonunda etkili genlerin yanı sıra, immünoreseptörler ile ilgili pek çok çalışma yapılmıştır. 22,[31][32][33][34][35][36][37][38][39][40][41] Tedavi edilen ve edilmeyen periodontitisli hastalarda yapılan uzun dönemli çalışmalara göre periodontitisin ilerlemesinde kişisel değişiklikler olduğu belirlenmiştir. 17,42,43 Löe ve arkadaşları, 17 ağız bakımının bulunmadığı veya zayıf günlük mikrobiyal dental plak kontrolüne sahip Sri Lanka çay bitkisi işçileri üzerinde 15 yıl süren çalışmaları sonucunda, toplumun %81'inde orta ve %8'inde hızlı seviyede periodontal hastalık ilerlemesi görülürken, %11'inde ise periodontal hastalığın ilerlemediğini saptamışlardır.…”
Section: Peridontal Hastalıkta Genetik Faktörlerin Rolüunclassified
“…From bacterial mimicry with HLA (Ebringer et al 1983) and HLA dependent immunoreactivity to bacterial antigens (Buckley et al 1973) an association with periodontopathic bacteria can be assumed. The most striking associations with periodontitis were found for HLA-A24 (Amer et al 1988;Firatli et al1996;Klouda et al 1986). Negative associations with periodontitis have been reported for HLA-A10 (Amer et al 1988;Klouda et al 1986).…”
Section: Introductionmentioning
confidence: 97%
“…The most striking associations with periodontitis were found for HLA-A24 (Amer et al 1988;Firatli et al1996;Klouda et al 1986). Negative associations with periodontitis have been reported for HLA-A10 (Amer et al 1988;Klouda et al 1986). Shapira et al (1994) found no significant difference in HLA-A, B, C, DR and DQ antigens between patient and control group.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation